Inflammatory myofibroblastic tumour of genitourinary system - Muhammad Nauman; Asad Shahzad Hasan; Gauhar Sultan; Pardeep Kumar; Mudassir Hussain; Altaf Hashmi (Journal of the Pakistan Medical Association, 2021)
We describe two cases of inflammatory myofibroblastic tumor (IMT) involving genitourinary system. One patient with mass of urinary bladder presented with lower abdominal pain. Other presented with a mass involving right kidney presented with right flank pain. At time there are no specific guidelines exist for the management of inflammatory myofibroblastic tumors. In this case series we will discuss the work-up and management approaches done for each case. Continuous...